LE BASSIN DÉVONO-DINANTIEN DE MECHRAA BEN ABBOU: BASSIN PULL APART SUR DÉCROCHEMENT DEXTRE (REHAMNA SEPTENTRIONAUX, MAROC) - Kholaiq, Mariame; Saber, Najib; Zahour, Ghalem (European Scientific Journal, ESJ, 2015)
The structuring of the Mechra Ben Abbou region during the Hercynian orogeny is intimately linked to the history of the Devonian- Dinantian basin. The basin sedimentation has been guided by the main fault movements limiting the Gada Jennabia unit; The Foum El Mejez fault in the East and the Leffaid faultin the West. In fact, the Foum El Mejez fault is a dextral strike-slip who undergoes virgation to open a pull apart basin in the Upper Visean. During different phaseshercynian, the visean basin is experiencing a complex tectonic combining fold and fault movements with the establishment of basic igneous rocks. In the present work, we study the various structures found in the region to reconstruct the history of the Mechraa Ben Abboubasin and propose a consistent conceptualmodel.